(untitled) (Scientific journal of the Fergana State University, 2022)
At the Ustyurtgaz Chemical Plant, the composition of methane pyrolysis waste was determined, scientific research was carried out on the production of road, roofing bitumen by introducing heavy pyrolysis resins - PS, coke extraction from PS waste, PS added to road construction bitumen in an amount of 5-50%, led to deterioration of the properties of road construction bitumen.